Immersive imaginaries: Digital spaces as post place care - Dara Ivanova; Thorben Peter Høj Simonsen (Digital Geography and Society, 2023)
With the spread of digitalization, the spaces and imaginaries of healthcare are fundamentally changing, due, in part, to an increasing uptake of immersive technologies. Building on previous ethnographic work on the nature of placed care (Ivanova, 2020a; Simonsen, 2020) this paper explores two cases of immersive technology advances in the Netherlands and Denmark to better understand contemporary developments in digital healthcare, the virtual environments they afford, and the immersive experiences they seek to evoke. First, we offer ‘immersive imaginaries’ as a heuristic for exploring how ideas of immersion, placeless-ness, and futurity intersect as key stakeholders in the healthcare innovation industry articulate socio-technical solutions to healthcare problems, and to what effects. Second, and in drawing inspiration from feminist STS on care, we build on Ivanova's (2020b) conceptual work on ‘post place care’ to analyse the relations between place, technology, and care in experiences of immersion. These two points form the contribution of the paper and its ambition to engage with ongoing discussions in the field of digital geography about how to analyse and theorise digital spaces of care.